Phosphorylation of TIP3 Aquaporins during Phaseolus vulgaris Embryo Development - Daniels, Mark J. (Cells, 2019)
The membrane phosphoproteome in plant seed changes dynamically during embryo development. We examined the patterns of Phaseolus vulgaris (common bean) seed membrane protein phosphorylation from the mid-maturation stage until two days after germination. Serine and threonine phosphorylation declined during seed maturation while tyrosine phosphorylation remained relatively constant. We discovered that the aquaporin PvTIP3;1 is the primary seed membrane phosphoprotein, and PvTIP3;2 shows a very low level of expression. The level of phosphorylated Ser7 in PvTIP3;1 increased four-fold after seed maturation. Since phosphorylation increases water channel activity, we infer that water transport by PvTIP3;1 is highest in dry and germinating seeds, which would be optimal for seed imbibition. By the use of isoform-specific, polyclonal peptide antibodies, we found that PvTIP3;2 is expressed in a developmental pattern similar to PvTIP3;1. Unexpectedly, PvTIP3;2 is tyrosine phosphorylated following seed maturation, which may suggest a mechanism for the regulation of PvTIP3;2 following seed germination. Analysis of protein secondary structure by circular dichroism spectroscopy indicated that the amino-terminal domain of PvTIP3;1 is generally unstructured, and phosphorylation increases polyproline II (PPII) helical structure. The carboxy-terminal domain also gains PPII character, but in a pH-dependent manner. These structural changes are a first step to understand TIP3 aquaporin regulation.